2015
DOI: 10.1002/ijc.29396
|View full text |Cite
|
Sign up to set email alerts
|

Frequency and phenotypic spectrum of germline mutations in POLE and seven other polymerase genes in 266 patients with colorectal adenomas and carcinomas

Abstract: In a number of families with colorectal adenomatous polyposis or suspected Lynch syndrome/HNPCC, no germline alteration in the APC, MUTYH, or mismatch repair (MMR) genes are found. Missense mutations in the polymerase genes POLE and POLD1 have recently been identified as rare cause of multiple colorectal adenomas and carcinomas, a condition termed polymerase proofreading‐associated polyposis (PPAP). The aim of the present study was to evaluate the clinical relevance and phenotypic spectrum of polymerase germli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
96
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(100 citation statements)
references
References 41 publications
1
96
0
2
Order By: Relevance
“…48 In an analysis of 266 unrelated probands with polyposis or who met the Amsterdam criteria, a POLE mutation was found in 1.5% of patients. 50 Novel variants for both POLD1 and POLE have been identified in individuals with CRC, broadening the phenotypic spectrum of POLD1-and POLE-associated polyposis. 46,51 Presently, for carriers of POLD1 and POLE mutations, the panel recommends similar management strategies as described for carriers of AXIN2 mutations (see GENE-7; page 1470).…”
Section: Pold1 and Pole Mutationsmentioning
confidence: 99%
“…48 In an analysis of 266 unrelated probands with polyposis or who met the Amsterdam criteria, a POLE mutation was found in 1.5% of patients. 50 Novel variants for both POLD1 and POLE have been identified in individuals with CRC, broadening the phenotypic spectrum of POLD1-and POLE-associated polyposis. 46,51 Presently, for carriers of POLD1 and POLE mutations, the panel recommends similar management strategies as described for carriers of AXIN2 mutations (see GENE-7; page 1470).…”
Section: Pold1 and Pole Mutationsmentioning
confidence: 99%
“…The CRC risk of FCCTX patients is double that of the general population (a third of that for Lynch syndrome patients), and FCCTX families lack extracolonic cancers (Lindor et al, 2005). The genetic basis of FCCTX remains unknown, however, recent investigations suggest that it may, like LLS, be a heterogeneous condition with mutations in several genes responsible (Nieminen et al, 2014;Schulz et al, 2014;Spier et al, 2015;Wei et al, 2015).…”
Section: Familial Colorectal Cancer Type Xmentioning
confidence: 99%
“…Many patients have a few dozen colorectal adenomas, while some patients have been reported to have no adenomas. As extracolonic manifestations, duodenal adenomas/cancers and brain tumors have been reported to develop in patients with PPAP carrying mutation of the POLE gene 20) and endometrial cancers, breast cancers, and brain tumors have been reported to develop in patients with PPAP carrying mutations of the POLD1 gene 21) . Tumors of the large intestine (colorectal adenomas and cancers) in PPAP are histologically indistinguishable from these tumors in sporadic cases.…”
Section: Polymerase Proofreading-associated Polyposis (Ppap)mentioning
confidence: 99%
“…Hideyuki Ishida 1) , Tatsuro Yamaguchi 2) , Kohji Tanakaya 3) , Kiwamu Akagi 4) , Yasuhiro Inoue 5) , Kensuke Kumamoto 6) , Hideki Shimodaira 7) , Shigeki Sekine 8) , Toshiaki Tanaka 9) , Akiko Chino 10) , Naohiro Tomita 11) , Takeshi Nakajima 12) , Hirotoshi Hasegawa 13) , Takao Hinoi 14) , Akira Hirasawa 15) , Yasuyuki Miyakura 16) , Yoshie Murakami 17) , Kei Muro 18) , Yoichi Ajioka 19) , Yojiro Hashiguchi 20) , Yoshinori Ito 21) , Yutaka Saito 22) , Tetsuya Hamaguchi 23) , Megumi Ishiguro 24) , Soichiro Ishihara 9) , Yukihide Kanemitsu 25) , Hiroshi Kawano 26) , Yusuke Kinugasa 27) , Norihiro Kokudo 28) , Keiko Murofushi 29) , Takako Nakajima , Narikazu Boku 23) , Takahiro Fujimori 39) , Michio Itabashi 40) , Nobuo Koinuma 41) , Takayuki Morita 42) , Genichi Nishimura 43) , Yuh Sakata 44) , Yasuhiro Shimada 45) , Keiichi Takahashi 2) , Shinji Tanaka 46) , Osamu Tsuruta 47) , Toshiharu Yamaguchi 48)…”
unclassified